ASSESSMENT OF FEAR AND STRESS BY THE ELDERLY IN THE NEW CORONAVIRUS PANDEMIC: A CROSS-SECTIONAL STUDY - Pereira, Joyce Regina; Fernandes, Daiane de Souza; Aguiar, Viviane Ferraz Ferreira de; Sousa, Fabianne de Jesus Dias de (Cogitare Enfermagem, 2022)
Objective: to identify the main fears and level of stress regarding the New coronavirus pandemic in the aged. Method: cross-sectional, analytical study based on a non-probability sample by convenience composed of 25 elderly users of a public square in the municipality of Belém, Pará, Brazil, conducted from January to June 2021. The sociodemographic questionnaire, New coronavirus fear scale, and perceived stress scale were applied. The parametric t-test (p<0.05) was used. Results: the average age was 67.6 years, predominantly female (72%). It was evidenced that the elderly presented a moderate level of fear (p0.001) related to the fear of COVID-19 (t=0.26). Moderate level of perceived stress (p0.001) related to irritability caused by the out-of-control situation (t=0.00) prevailed. Conclusion: perceiving fear and stress in the elderly contributes to the development of actions by professionals to promote mental health in times of pandemic.